Grown ups [videorecording (DVD)] - Dugan, Dennis; Spade, David; James, Kevin, 1965-; Sandler, Adam; Rock, Chris; Bello, Maria, 1967-; Schneider, Rob; Hayek, Salma, 1966- (Sony Pictures Home Entertainment, 2010)
Five friends and former teammates reunite on the Fourth of July weekend to honor the passing of their former high school basketball coach.